Bank financing and innovative development of Russian circumpolar area: An empirical investigation. Issue 3 (5th March 2018) - Pogodaeva, Taisya; Baburina, Natalia; Dmitrieva, Anna
Abstract : Purpose: The purpose of this paper is to study the impact of bank financing on innovative development of Russian circumpolar area and identifying the barriers to its development. Design/methodology/approach: Using the abstract-logical method and a set of methods of economic, statistical and econometric analysis (panel data analysis) the authors examine the role of financial intermediaries in innovative development of Russia and Russian arctic regions. Findings: The key financial intermediaries in the Russian economy have historically been the banks, which are, at the same time, as it follows from the analysis above, inertly participating in the innovative development financing in the Russian circumpolar regions. Assessment of the potential intensification of the role of banks in the innovative ecosystems has shown that, despite the development of institutional conditions of banks' resource base compounding and the development of funding, high risks of innovation, multiplying in a volatile external environment, prevent the inflow of bank capital into the innovation sector. Research limitations/implications: Main limitation is the inability of panel data to capture long-term impacts of bank financing on innovative development of Russian circumpolar area. Practical implications: The results suggest that the intensification of the banks' participation in financing innovation and overcoming the existing challenges will enable to stimulate the process of innovation development of the circumpolar zone in Russia. Originality/value: There is no study evaluating the impact of bank financing on innovative development of Russian arctic regions.